The Effect of Technology-Based PBL Learning on Junior High School Students' Mathematical Representation Ability in Data Centralisation Material - Desi Nargis Nargis; Muslim Muslim; Syarifudin Syarifudin; Arif Hidayad; Arif Rahman Hakim (JURNAL PENDIDIKAN MATEMATIKA, 2025)
Abstract: The low level of students' mathematical representation ability became the background of this study. The research aimed to analyse the effect of implementing the Problem-Based Learning (PBL) model assisted by interactive PowerPoint media and Microsoft Excel on students' mathematical representation ability. The research method used was a quasi-experiment with a pretest-posttest control group design. The sample consisted of 40 eighth-grade students divided into an experimental group and a control group. The research instrument was a mathematical representation ability test that had been validated and proven reliable. Data were analysed using a t-test and N-Gain calculation. The results showed that the N-Gain score in the experimental class reached 0.82 (high category), while in the control class it was only 0.22 (low category). The difference was statistically significant (t = 20.316; p < 0.000). Thus, it can be concluded that integrating PowerPoint and Excel into the PBL model is effective in improving students' mathematical representation ability, particularly in presenting data in the form of graphs and tables. This research implies that a PBL model supported by digital media can serve as an innovative alternative for mathematics learning. Keywords: Problem Based Learning (PBL); Microsoft Excel; Mathematical Representation; Data Centralization; Quasi-Experiment